Analysis of Trends in Library Archive Digital Management from 2019 to 2023 - Rosyani, Widha; Yuadi, Imam (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research aims to understand and find problems related to managing library digital archives using bibliometric analysis. Bibliometric analysis was carried out on journals on the topic